2007
DOI: 10.1128/aem.02553-06
|View full text |Cite
|
Sign up to set email alerts
|

Rugosity in Grimontia hollisae

Abstract: Grimontia hollisae, formerly Vibrio hollisae, produces both smooth and rugose colonial variants. The rugose colony phenotype is characterized by wrinkled colonies producing copious amounts of exopolysaccharide. Cells from a rugose colony grown at 30°C form rugose colonies, while the same cells grown at 37°C form smooth colonies, which are characterized by a nonwrinkled, uncrannied appearance. Stress response studies revealed that after exposure to bleach for 30 min, rugose survivors outnumbered smooth survivor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…2006), Vibrio cholerae (Ali et al. 2002) and Grimontia hollisae (formerly Vibrio hollisae) (Curtis et al. 2007) have shown that strains expressing the rugose phenotype impart: (i) a resistance to desiccation and antimicrobial agents such as hypochlorite; (ii) an increased ability to form biofilms; and (iii) the reversible rugose to smooth colony phase variation that was originally described by Farmer et al.…”
Section: Control In Manufacturing Environmentmentioning
confidence: 99%
“…2006), Vibrio cholerae (Ali et al. 2002) and Grimontia hollisae (formerly Vibrio hollisae) (Curtis et al. 2007) have shown that strains expressing the rugose phenotype impart: (i) a resistance to desiccation and antimicrobial agents such as hypochlorite; (ii) an increased ability to form biofilms; and (iii) the reversible rugose to smooth colony phase variation that was originally described by Farmer et al.…”
Section: Control In Manufacturing Environmentmentioning
confidence: 99%
“…It is now well acknowledged that in most bacteria the rugosity is due to overproduction of exopolysaccharide (EPS) (2,4,9). Diverse genetic screens for genes essential for the rugose phenotype have identified many genes required for EPS synthesis, such as bcsABZC in Acetobacter xylinus, S. enterica serovar Typhimurium, and E. coli (10), pel in P. aeruginosa (16), vps in V. cholerae (17,18), and eps in B. subtilis, to name a few (19,20).…”
mentioning
confidence: 99%
“…Depending on the strain and the surrounding conditions, the morphology of colonies (morphotype) varies substantially (2,3). Colony morphotypes of well-studied bacteria, including Vibrio cholerae, Pseudomonas aeruginosa, Salmonella enterica serovar Typhimurium, Escherichia coli, and Bacillus subtilis, are either smooth or rugose (also called wrinkling), in general (4)(5)(6)(7)(8)(9)(10). The rugosity promotes persistence under unfavorable conditions, such as conditions of exposure to toxins, UV light, osmotic and oxidative stresses, low pH, low temperatures, and starvation (5,8,(11)(12)(13), and enhances virulence and transmission, such as adherence and invasion of epithelial cells (7,14,15).…”
mentioning
confidence: 99%
“…Detection and quantification of biofilms were performed with cultures grown in glass tubes (10 Â 75 mm) using the modified procedure as described by Mireles et al (2001), Solomon et al (2005), and Curtis et al (2007). The bacterial strains were grown overnight on LB agar plates, then were transferred to 5 ml LBNS broth using sterilized inoculating loops (3 mm diameter loop; half a loop of bacteria per tube), and incubated at 37 C or 28 C with shaking (150 rpm) for 48 h. The formation of biofilm (pellicles at the air-broth interface) was visually evaluated; the tubes were washed twice with PBS, air-dried for 30 min, stained with 0.1% crystal violet at room temperature for 30 min, and washed twice with distilled water.…”
Section: Biofilm Formation Assaymentioning
confidence: 99%